Unprecedented and unmasked: An analysis of how district policy documents frame special education during the COVID crisis - Woulfin, Sarah L.; Jones, Britney (Education Policy Analysis Archives, 2022)
COVID-19 school closures disrupted special education. In Fall 2020, districts sought to reopen schools, recover from the shocks of the pandemic, and implement special education to serve students with disabilities. Using policy document data from the United States’ 25 largest school districts, we surface patterns in how districts communicated problems and solutions related to special education for the 2020-21 school year. Drawing on concepts from framing theory, we analyzed messaging on special education embedded in 71 district policy documents. Specifically, we assessed the nature and foci of 520 special education policy frames. The 520 frames contained ideas on problems and solutions regarding special education. Results indicate that this set of districts foregrounded how to implement the compliance and intervention models of special education in their formal communication but devoted less attention to the equity model of special education. Districts rarely defined underlying problems in special education implementation amid pandemic schooling. We discuss potential consequences of these patterns in messaging on special education. Finally, we present evidence- and theory-based recommendations for policy, practice, and scholarship on the implementation of special education with attention to recuperating from pandemic-related impacts.